Lung abscess caused by Streptococcus pneumoniae serotype 6B. (2018) - Ito, Yuhei; Toyoshima, Hirokazu; Suzuki, Takehiro; Iwamoto, Keisuke; Sasano, Hajime; Itani, Hidetoshi; Kondo, Shigeto; Tanigawa, Motoaki
Abstract: Lung abscess has been considered to be a rare complication of pneumococcal infection, and most cases are reported to be Streptococcus pneumoniae serotype 3. A 67-year-old man presented with fever and was diagnosed to have lung abscess caused by S. pneumoniae serotype 6B. The minimal inhibitory concentration (MIC) of penicillin for the isolate was 1 μg/mL. He was treated with high-dose intravenous sulbactam/ampicillin as definitive therapy based on susceptibility testing for S. pneumoniae and recovered successfully without surgical intervention. S. pneumoniae serotype 6B can cause lung abscess.